Experiment and Simulation Analysis of Dynamic Performance of Excavator Gearbox - Gao Ying; Peng Jinmin; Cheng Yuan; Zheng Wenbiao; Wu Xuanzhong (Jixie chuandong)
The modal parameters of the gearbox have great influence on the vibration characteristics of the transmission and the whole machine. Combining with the finite element method and the testing technology,the free modal analysis and test of the XG958 H type excavator gearbox are carried out and modal parameters are obtained. The ANSYS Workbench analysis software is used to simulate the modal of the gearbox. At the same time,based on the LMS test and analysis system,the parameters of each stage of the gearbox are identified by the least square method. The results show that the results from the two methods are basically the same and the maximum error is 7. 54%,which verifies the reliability of the LMS experimental method and the ANSYS Workbench simulation,and the reference to avoid the resonance frequency when the gearbox is working is provided.